2006
DOI: 10.1289/ehp.9102
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Lifetime Occupational Lead Exposure and Risk of Parkinson’s Disease

Abstract: BackgroundSeveral epidemiologic studies have suggested an association between Parkinson’s disease (PD) and exposure to heavy metals using subjective exposure measurements.ObjectivesWe investigated the association between objective chronic occupational lead exposure and the risk of PD.MethodsWe enrolled 121 PD patients and 414 age-, sex-, and race-, frequency-matched controls in a case–control study. As an indicator of chronic Pb exposure, we measured concentrations of tibial and calcaneal bone Pb stores using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 26 publications
3
104
1
1
Order By: Relevance
“…30 Lead is a well-known toxic heavy metal that is associated with several neurodegenerative disorders, including PD: Coon et al studied 121 PD patients and showed that occupational lead exposure is a risk factor for PD. 35 Part of the toxic response to Pb(II) exposure is the formation of aggresometype inclusions in target cells, a process which was shown to be controlled by α-syn, among other proteins. 36 Because copper is redox-active in the brain, it has been hypothesized that dysregulation of copper homeostasis, for example, through abnormal binding to α-syn, could catalyze the formation of noxious ROS and thus contribute to neurodegeneration via increased oxidative stress.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…30 Lead is a well-known toxic heavy metal that is associated with several neurodegenerative disorders, including PD: Coon et al studied 121 PD patients and showed that occupational lead exposure is a risk factor for PD. 35 Part of the toxic response to Pb(II) exposure is the formation of aggresometype inclusions in target cells, a process which was shown to be controlled by α-syn, among other proteins. 36 Because copper is redox-active in the brain, it has been hypothesized that dysregulation of copper homeostasis, for example, through abnormal binding to α-syn, could catalyze the formation of noxious ROS and thus contribute to neurodegeneration via increased oxidative stress.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Neuromelanin in the substantia nigra also accumulates an extremely high amount of lead. Such a high influx of lead into dopaminergic neurons could underlie the reported increase of risk for Parkinson's disease in occupational exposure to lead (29). In the past, people were exposed to organic lead by leaded gasoline, and that lead could cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of exposure to lead and iron showed no increased risk compared to exposure to lead alone [322]. Using the same subjects, these authors assessed whole body lifetime lead exposure by measurements of bone lead stores in combination with occupational history and reported an increased risk of PD for the 4 th quartile of whole body lifetime lead exposure compared to the 1 st quartile (OR 2.27, 95% CI 1.13-4.55) [383].…”
Section: Metalsmentioning
confidence: 98%